Jurisdiksi Dunia Maya (Cyberspace) Dalam Sistem Hukum Nasional Abad XXI - Ibrahim R (Jurnal Hukum IUS QUIA IUSTUM, 2003)
The development of global information technology, to have an effect on using of internet for e-commerce, e-business, e-banking activities, also give of cyber liberty both of commercial cyber liberty and of civil cyber liberty, where, the man can be acesy, free, and quick to do transaction without they have to meet by face to face, to transfer and to acsess of information, etc. But it must be considered the cyber liberty by internet can be wiss used for doing cyber threat, cyber terorism and cyber talking, also for somebody do crime whichdestroyed of moral easily, as gambling prostitution, and pomografy. The jurisdiction of dispute settlement still debatable, because of the dispute settlement construction again the problems appeare must be efforted the way out continuously while we want for the regulation about it.